Acute medications’ intake for migraine: a one-year report in patients undergoing first evaluation at a third level Italian headache center - Bonura, Adriano; Alesina, Alessandro; Sapio, Elisabetta; Brunelli, Nicoletta; Marcosano, Marilena; Altamura, Claudia; Vernieri, Fabrizio (Frontiers in Neurology, 2024)
Background: Headache disorders, particularly primary headaches like migraine and tension-type headache, still remain underdiagnosed and undertreated despite their high prevalence and significant impact on quality of life. In recent years, several specific medications targeting key pathways in the pathophysiology of migraine have been developed. Despite this advancement, numerous studies indicate that non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics remain the most commonly used drugs. This study focused on the use of NSAIDs and simple analgesics as acute treatments for migraine among patients at a tertiary headache center.Methods: A retrospective observational study was conducted at the Fondazione Policlinico Universitario Campus Bio-Medico throughout 2022. . Data were collected on the type and frequency of headaches, the usage and dosage of NSAIDs and other medications, and changes in their use at follow-up visits. Statistical analyses were performed to evaluate the efficacy and determinants of NSAID consumption and headache frequency changes.Results: Two hundred and eightythree patients diagnosed with migraine undergoing their first examination at our center were enrolled. Initially, 58.7% of patients used NSAIDs or simple analgesics, which decreased to 46.6% 3 months after, while triptan use increased from 65.1% to 72.8%. Changes in prophylactic therapies were significantly associated with a decrease in NSAID intake (W=834.000, p=0.004) and in headache frequency (W=5960.5, p=0.003). Specifically, the addition of topiramate or amitriptyline was associated with a reduction in NSAID use and headache frequency. Even pain freedom after the intake of NSAIDs improved from 55.2% to 79.4% of cases at follow-up.The study highlights the importance of appropriate diagnosis and tailored treatment strategies in the management of primary headaches. It underscores the need for specialized care to enhance treatment efficacy and patient outcomes, demonstrating that adjustments in prophylactic therapy can significantly reduce NSAID intake and improve headache care. This reinforces the role